2011
DOI: 10.1021/jf1045987
|View full text |Cite
|
Sign up to set email alerts
|

New Bioactive Orange Pigments with Yellow Fluorescence from Monascus-Fermented Dioscorea

Abstract: Red mold dioscorea (RMD) is a fermented product of Monascus purpureus NTU 568 using dioscorea as culture substrate. To investigate the bioactive components of RMD, six orange pigments including four new azaphilones with yellow fluorescence, monapilol A-D (1-4), and known monascorubrin (5) and rubropunctatin (6) were isolated and characterized. Structural elucidation of new isolates was based on nuclear magnetic resonance ((1)H NMR, (13)C NMR, COSY, HMQC, and HMBC) and other spectroscopic analyses. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…Monascin (yellow), monascorubrin (orange), monascorubramine (red), monapurone A-C (yellow), monasphilone A and B (yellow), ankaflavin (yellow), rubropunctamine (purple-red), rubropunctatin (orange), monopilol A-D (yellow), citrinin (yellow), 9-(1-hydroxyhexyl)-3-(2-hydroxypropyl)-6a-methyl-9,9a-dihydrofuro [2,3-h] isoquinoline-6,8(2H,6aH)-dione (red), uncharacterized (red) [56][57][58][59][60][61] Monascus ruber…”
Section: Monascus Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Monascin (yellow), monascorubrin (orange), monascorubramine (red), monapurone A-C (yellow), monasphilone A and B (yellow), ankaflavin (yellow), rubropunctamine (purple-red), rubropunctatin (orange), monopilol A-D (yellow), citrinin (yellow), 9-(1-hydroxyhexyl)-3-(2-hydroxypropyl)-6a-methyl-9,9a-dihydrofuro [2,3-h] isoquinoline-6,8(2H,6aH)-dione (red), uncharacterized (red) [56][57][58][59][60][61] Monascus ruber…”
Section: Monascus Speciesmentioning
confidence: 99%
“…Several studies have revealed the fungal pigments as a potential anticancer drug. Pigments of Monascus species (M. purpureus and M. pilosus) such as monascin, ankaflavin, monaphilone A-B, monasphilone A-B, monapilol A-D, and monapurone A-C have been proved to possess anticancer/antitumor potential against different types of cancers, such as mouse skin carcinoma, human laryngeal carcinoma, human colon adenocarcinoma, human hepatocellular carcinoma, and pulmonary adenocarcinoma (Figure 12) [32,[56][57][58]204,205]. Besides Monascus, pigments from other fungi such as norsolorinic acid from A. nidulans, shiraiarin from Shiraia bambusicola, alterporriol K, alterporriol L, and alterporriol M from Alternaria spp., benzoquinone from Pigments from different taxonomic groups of fungi having promising anticancer or antitumor potential, re-drawn from [32,[56][57][58]62,68,88,89,113,204,205].…”
Section: Fungal Pigments As Anticancer Agentsmentioning
confidence: 99%
“…Currently, 9 Monascus species have been internationally recognized in the genus; these are M. argentinensis , M. eremophilus , M. floridanus , M. lunisporas , M. pallens , M. pilosus , M. purpureus , M. ruber , and M. sanguineus (Shao and others ). Among them, M. pilosus , M. purpureus , and M. ruber are the most common species used in industrial applications (Hsu and others ; Cheng and others ; Lian and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this notion, overexpression of Skp2 promotes resistance to ATRA and prevents p27 accumulation in breast cancer cells (Dow et al, 2001). Hsu et al (2011) found that gallic acid markedly reduced cell growth of human breast cancer cells and induced cell cycle arrest by inhibition of Skp2 and attenuation of Skp2–p27 association as well as reduction of p27 ubiquitination. Huang et al (2008) reported that EGCG (Epigallocatechin-3-gallate), the main constituent of green tea, inhibited human breast cancer cell growth in part through down-regulation of Skp2 expression and accumulation of p27.…”
Section: Skp2 Inhibition Is a Novel Strategy For Breast Cancer Treatmentmentioning
confidence: 99%